Gender Leadership and the Dynamics of Women's Leadership in Islamic Educational Institutions - Mohammad Dendy Musthofa; Abu Hasan Agus R (STKIP Pesisir Selatan, 2026)
This study uses a qualitative approach with the aim of understanding the phenomenon of Gender Leadership and the Dynamics of Women's Leadership in Islamic Educational Institutions in depth through the perspectives of the participants. Data were collected through in-depth interviews, observations, focus group discussions (FGDs), and documentation, involving the principal, teachers, and parents as the primary sources of information. Data analysis was conducted thematically by following the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate several important aspects, namely Gender Leadership in the Perspective of Islamic Education which emphasizes the compatibility of Islamic values with the practice of women's leadership; Challenges of Women's Leadership in a Gender Context which reflect cultural barriers and social stereotypes; and Support and Legitimacy of Ibu Nurul's Leadership which grows through concrete performance, collective participation, and effective communication with various elements of the madrasah. This study contributes to theoretical, practical, and policy implications. Theoretically, this study enriches the study of gender and leadership in Islamic education, especially in the context of elementary madrasahs. Practically, the research findings can serve as a reference for other madrasah principals in developing leadership patterns that are inclusive, participatory, and responsive to the needs of the school community. Meanwhile, from a policy perspective, this research provides input for policymakers to further open up leadership opportunities for women in Islamic educational institutions, while simultaneously reducing existing structural and cultural barriers. Thus, this research not only describes a phenomenon but also provides new insights into the issue of gender equality in Islamic educational leadership at MI Mirqotul Ulum, relevant for development in broader research settings.